Effects of a Pilot Church-based Intervention to Reduce HIV Stigma and Promote HIV Testing among African Americans and Latinos - Derose, Kathryn P. (AIDS Behav, 2016)
HIV-related stigma and mistrust contribute to HIV disparities. Addressing stigma with faith partners may be effective, but few church-based stigma reduction interventions have been tested. We implemented a pilot intervention with 3 Latino and 2 African American churches (4 in matched pairs) in high HIV prevalence areas of Los Angeles County to reduce HIV stigma and mistrust and increase HIV testing. The intervention included HIV education and peer leader workshops, pastor-delivered sermons on HIV with imagined contact scenarios, and HIV testing events. We surveyed congregants at baseline and 6 month follow-up (n=1235) and found statistically significant (p<.05) reductions in HIV stigma and mistrust in the Latino intervention churches but not in the African American intervention church nor overall across matched African American and Latino pairs. However, within matched pairs, intervention churches had much higher rates of HIV testing (p< .001). Stigma reduction and HIV testing may have synergistic effects in community settings.